The human development in Tunisia: synthetic indicators (HDI) and regional disparities - Bousnina Adel (Journal of North African Economies, 2025)
The aim of this article is, at first, to analyze the performances and results of the experience of human development in Tunisia. The first part will be centered on the progress of two synthetic indicators: the HDI (Human Development Indicator, as defined by UNDP) and our own approach based on synthetic indicators of human development (Synthetic HDI). In the second part of the article, our aim is, to study the regional disparities and territorial inequalities of human development in Tunisia: first, we will realize Factorial components analysis. Then, we will analyze the progress of synthetic indicators of human development in every region, thanks to our approach based on the HDI (Human Development Index), the HPI ((Human poverty Indicator) and a synthetic indicator of human development in every region and governorate.